1998
DOI: 10.1021/jp980060f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents on the Photoenolization ofo-Methylanthrone at Low Temperatures. Evidence for H-Atom Tunneling from Nonequilibrating Triplets

Abstract: The reactivity of 1,4-dimethylanthrone (1,4-MAT) and 1,4-dimethylanthrone-d 8 (1,4-DMAT) toward hydrogen transfer was investigated in methylcyclohexane (MCH), ethanol (EtOH), and 2,2,2-trifluoroethanol (TFE) by comparing their triplet-state emission spectra and lifetimes with those of compounds without the o-methyl substituent. A predominantly n,π* lowest triplet state in nonpolar solvents such as MCH changes toward a less reactive π,π* configuration in polar solvents such as EtOH and TFE. In EtOH, 1,4-DMAT ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 87 publications
(202 reference statements)
2
22
1
Order By: Relevance
“…This is the case of the photoenolization of 1,4‐dimethylanthrone (1,4‐MAT) and 1,4‐dimethylanthrone‐ d 8 (1,4‐DMAT) in several solvents. Garcia‐Garibay and coworkers have experimentally shown that deuterium transfer of the triplet ketone 3 K in 1,4‐DMAT at very low temperatures (ca. 15–90 K) is slow enough to compete with radiative and thermal decay, so that phosphorescence emission was detected.…”
Section: Kies As a Function Of Energymentioning
confidence: 99%
“…This is the case of the photoenolization of 1,4‐dimethylanthrone (1,4‐MAT) and 1,4‐dimethylanthrone‐ d 8 (1,4‐DMAT) in several solvents. Garcia‐Garibay and coworkers have experimentally shown that deuterium transfer of the triplet ketone 3 K in 1,4‐DMAT at very low temperatures (ca. 15–90 K) is slow enough to compete with radiative and thermal decay, so that phosphorescence emission was detected.…”
Section: Kies As a Function Of Energymentioning
confidence: 99%
“…All triplet decays were relatively complex but could be fit reasonably to a double exponential, with rates k 1 and k 2 and preexponential factors I 1 and I 2 . Although solvation effects, slightly different conformations, and mixing of nearby π,π* states may contribute to the observed nonexponentiality, , the greatest deviations were observed at the lowest temperatures. Given the complexity of the experimental data, to carry out a qualitative but insightful analysis of deuteurium transfer using eq 1, the average decay rates of 1a − c and 2a − c were calculated according to eq 2, with the contribution of each component obtained from the ratios I 1 / k 1 and I 2 / k 2 2d…”
mentioning
confidence: 93%
“…Our interest in reactions that occur under highly restricted molecular motion in crystalline and amorphous solids has led us to analyze transformations that occur at extremely low temperatures. Recent examples include the photoenolization of conformationally restricted ortho -methyl aryl ketones, which are illustrated in Scheme with 5,8-dimethyltetralone ( 1a ) .…”
mentioning
confidence: 99%
See 2 more Smart Citations